Biochemical monitoring in sports: focal points for improvement - G. Makarova; E. Achkasov; I. Baranovskaya (National Electronic Information Consortium (NEICON), 2020)
Literature data analysis along with decades of experience in sports medicine (biochemistry of sports included) enabled us to classify and explain key points that would be appropriate to consider when conducting biochemical research in sports, but in doing so we believe that the relevant research studies make just a part of a comprehensive medical and pedagogical monitoring.